Clinical characteristics and prognosis of 16 relapsed/refractory B-cell malignancy patients with CAR T-cell-related hyperferritinaemia - Zhou, Lanlan; Yu, Nanzhou; Li, Tongjuan; Ji, Hongyan; Jiang, Lijun; Wang, Di; Xu, Bin; Zhou, Xiaoxi (Frontiers in Oncology, 2022)
With the success of chimeric antigen receptor-modified (CAR) T-cell therapy for relapsed/refractory (r/r) B-cell malignancies, severe complications after CAR T-cell infusion have emerged as nonnegligible prognosis-related factors. However, the prognosis of patients with CAR T-cell-related hyperferritinaemia (HFA) is unclear. We report the efficacy and safety of CAR T-cell therapy in 16 r/r B-cell malignancy patients with CAR T-cell-related HFA. The rates of serum ferritin levels above 10,000 ng/ml during CAR T-cell therapy were 6.2% and 14.3% in B-cell non-Hodgkin’s lymphoma (B-NHL) and acute B lymphocyte leukemia (B-ALL), respectively. These patients were characterized by an extremely high tumor burden and a high rate of extranodal involvement. In lymphoma, the complete remission (CR) rate was 37.5% (3/8), which was lower than that in the control group with the lowest value of ferritin (CR was 87.5% (7/8), P=0.0406), and it could also be seen that the OS of the control group (1-year OS rate 100%) had a better trend than HFA group (1-year OS rate 50%). In the B-ALL patients, the OS of the control group (1-year OS rate 100%) was higher than HFA group (1-year OS rate 45%, P=0.0189), although there was no significant difference in CR rate. High-grade CRS (≥3) occurred in 56.25% of the patients, and the mortality rate was 56.25%, which was significantly higher than control group (12.5% and 12.5%, P=0.009). The peak serum ferritin level in the patients who died of CRS was significantly higher than others (P=0.0168). Regardless of whether the CAR T-related MAS diagnostic criteria were met, there was no significant difference in ORR and OS in HFA group, however patients with MAS showed a higher rate of high-grade CRS. Interestingly, in our study, glucocorticoid intervention in HFA group showed little impact on expansion of CAR-T cells, whether compared with control group or compared within HFA group by dividing patients into high and low dosage subgroups based on the median dose of glucocorticoid. High mortality was observed in patients with CAR T-cell-related HFA. Early glucocorticoid intervention might be worth trying to improve the safety of CAR T therapy in these patients.